Problematics Juridis Facilitation In Regional Development Planning Process (Study of Kendal Regency Research and Development Planning Agency) - Izzuddin Latif; Widayati Widayati (Jurnal Daulat Hukum, 2019)
Facilitation of Development Planning is very urgent and vital as an instrument to increase effectiveness in building synergy in terms of regional development in accordance with the mandate of the law on national development planning, namely in accordance with Permendagri Number 86 of 2017. Kendal Regency Facilitation Process by the Central Java provincial government those that have been implemented well will produce legal products that are able to explain the central government's development programs and there will not be problems in the future. The problems of Regional Development Planning, which have been carried out by the Central Java provincial government, are still much sought to be in accordance with the conditions and needs and well implemented in accordance with the laws and regulations, the need for a better solution to avoid future problems ; Time problems that are less effective, and so that scheduling is done in great detail and in a short amount of time, to improve the performance and effectiveness of facilitation. Regarding the issuance of the Minutes is not quite right than the issuance of the Governor's Decree, the Javanese provincial government should be publishing the provisions of the results of facilitation that have been carried out.The Kendal Regency Government also seeks to ask the provincial government to establish a governor's decree so that it can form the basis of the legal umbrella of regional development planning, which is in accordance with the substance of the Minister of Home Affairs Regulation No. 86 of 2017, relating to the Regional Development planning process in Kendal District, which was previously in 2016 has been amended by the new regulation by referring to Permendagri regulation No. 86 of 2017, Kendal District Government seeks to ask the Governor of Central Java as the provincial government to provide facilitation that is in accordance with Kendal Regency characteristics, with reference to the effectiveness of the time given so that the bureaucracy that is built can be effective and efficient.Keywords: Facilitation, Juridical, Regional Development Planning